Agency Banking and Operational Performance of Commercial Banks in Kenya - Mbugua, Veronicah Njambi (University of Embu, 2020)
Agency banking roll-out in Kenya was meant to address the low financial inclusion in Kenya. As per the 2009 National financial access survey, 32% Kenyans bankable population is still totally out of the financial services orbit. Difficulties in accessing financial services main drivers are; long distance to banking channels and relative high costs of accessing financial services. In a bid to bridge the financial access divide and improve its access among the most vulnerable sections of the society, the Kenya government through the central bank amended the finance Act 2009 to facilitate use of third parties by banks to provide banking services. This study sought to establish the contribution of agency banking to operational performance of commercial banks in Kenya. The researcher was guided by objectives; to establish the impact of agency banking to operational performance of commercial banks in Kenya; to determine the operational challenges facing agency banking in Kenya and to establish the factors leading to the growth of agency banking. Data was collected by use of questionnaire. Data was analyzed and presented using descriptive statistical tools. The results were presented in a continuous prose form. The study showed that liquidity availability in the outlets affected banks performance in addition to leading to frustrated customers. The study also found out that agency infrastructure cost and security was a major influence to banks performance. The study therefore recommends that, banks should give more attention to security and find better ways of vetting their agents to ensure that large cash transaction are handled effectively